(untitled) - DuFrene, Debbie D.; Debbie D. DuFrene; Carol M. Lehman (Mason, OH, 2005)
In school and later as business professionals, learners will be asked to join teams. These may be permanent, high-powered, self-managed work teams or special-purpose groups that meet only long enough to tackle a specific problem. No matter what the team situation, this text helps readers build the vital skills to maximize individual contribution, understand team roles, overcoming conflict, negotiate solutions, evaluate outcomes, and think creatively. This guided process is a productive team experience that yields high-performance results - results that can be replicated in team settings in the workplace
Keywords: Teams in the workplace